MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN PEMAHAMAN PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH ALIYAH SALAFIYAH SAFI`IYAH TEBUIRENG JOMBANG - Kumala, Akhsinatul; Hosna, Rofiatul; Rohman, Fathur (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
This article aims to explain the application of the Discovery Learning model in improving understanding of the SKI subjects at MASS Tebuireng, learning SKI at MASS Tebuireng, and the factors. Inhibitors and supporters of discovery learning learning models. This study uses a qualitative approach using three data collection methods: observation, interviews, and documentation. To analyze the data, it was carried out through three prosedures, namely data reduction, data presentation, and drawing conclusions. The results show that the application of discovery learning learning model for SKI subjects at MASS Tebuireng has shown success. Institutions provide adequate facilities. Inhibiting factors are the large number of classes, the seating position is less regular, while the supporting factors are all related parties preparing the equipment needed in the class, a complete library, all students have textbooks, the class atmosphere is pleasant, and many students are active.